2000
DOI: 10.1111/j.1749-6632.2000.tb06713.x
|View full text |Cite
|
Sign up to set email alerts
|

Ga733/EpCAM as a Target for Passive and Active Specific Immunotherapy in Patients with Colorectal Carcinoma

Abstract: GA733/EpCAM is an oncofetal antigen abundantly expressed in colorectal carcinoma. This antigen can spontaneously induce a humoral and cellular antitumor immunity and may therefore be a suitable target structure for immunotherapy. Patients with advanced colorectal carcinoma have been treated with monoclonal antibodies (MAb17‐1A) against this structure. The data indicate that the chimeric variant was not superior to the original mouse MAb. Addition of cytokines and chemotherapeutics may improve the therapeutic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 9 publications
(14 reference statements)
0
12
0
Order By: Relevance
“…The first antibody used in passive immunotherapy was edrecolomab, a murine IgG2a antibody targeting Ep-CAM (Sears et al, 1984;Riethmuller et al, 1994). The therapeutic effect of this antibody administered alone or in combination with chemotherapy or GM-CSF (Mellstedt et al, 2000) was not conclusive, but it showed a very benign safety profile (Fields et al, 2002;Punt et al, 2002;Hartung et al, 2005). To reduce immunogenicity and enhance antibodydependant cytotoxicity, complement dependant cytotoxicity and serum half-life, humanised antibodies ING-1 (de Bono et al, 2004), 3622W94 (Abdullah et al, 1999;Martin et al, 1999) and fully human IgG1 antibody MT201 (adecatumumab) (Naundorf et al, 2002;Brischwein et al, 2005) were developed.…”
Section: Discussionmentioning
confidence: 99%
“…The first antibody used in passive immunotherapy was edrecolomab, a murine IgG2a antibody targeting Ep-CAM (Sears et al, 1984;Riethmuller et al, 1994). The therapeutic effect of this antibody administered alone or in combination with chemotherapy or GM-CSF (Mellstedt et al, 2000) was not conclusive, but it showed a very benign safety profile (Fields et al, 2002;Punt et al, 2002;Hartung et al, 2005). To reduce immunogenicity and enhance antibodydependant cytotoxicity, complement dependant cytotoxicity and serum half-life, humanised antibodies ING-1 (de Bono et al, 2004), 3622W94 (Abdullah et al, 1999;Martin et al, 1999) and fully human IgG1 antibody MT201 (adecatumumab) (Naundorf et al, 2002;Brischwein et al, 2005) were developed.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its constitutive expression, blockade of EpCAM by specific antibodies has been reported to be of therapeutic benefit [11,12]. Moreover, self-tolerance towards EpCAM can be broken, so that the generation of EpCAM-specific T cells can open a new therapeutic option [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Ep-CAM expression portends tumor differentiation and is an independent predictor of survival in breast cancer (10,(12)(13)(14). Highly expressed on the surface of many adenocarcinomas, ϳ85% of colorectal carcinomas express Ep-CAM, with more than 80% of tumor cells expressing Ͼ10 6 molecules/cell (15,16). Ep-CAM is also expressed on some normal tissues, but the density of antigen expression is much higher on tumor cells (17).…”
Section: Introductionmentioning
confidence: 99%